5PSQ-016 Safe use of antiplatelet medication: approaching the optimal dose of aspirin by pharmaceutical intervention - López-Álvarez, C (Eur J Hosp Pharm, 2018)
BACKGROUND: Based on available evidence and its benefit/risk balance, acetylsalicylic acid (ASA) is the first-line antiplatelet drug of choice for secondary prevention of cardiovascular events. It is recommended to be used at low doses, not exceeding 150 mg/day. This dosage has proved to be effective enough for the prevention of vascular events, both primary and secondary ones, whereas higher doses do not significantly increase the vascular protective effect but are associated with an increased risk of side-effects. PURPOSE: To identify all patients with maintenance doses of ASA greater than 150 mg/day and reduce these dosages to correct them according to the evidence. MATERIAL AND METHODS: Seven-month pre/post intervention study. The pharmacy service obtained the list of outpatients from the area on ASA treatment through the prescription data program. Data were exported to an Excel(®) spreadsheet where more than 150 mg/day doses were identified. This information was sent to the general practitioners (GPs) so they could modify the drug doses when required. The intervention impact was evaluated at the pharmacy service by reviewing the prescription of the patients sent in the Excel spreadsheet. The appropriateness of the maintenance dosage was checked and the modified or suspended prescription when more than 150 mg/day prescription, detected. RESULTS: There were 455 patients in the area on ASA treatment at high doses (>150 mg/day) for more than 2 months. A self-audit of 79.78% (363) patients was performed in a 3 month period, with a mean age of 73±11 (±SD) years, being 48% males. A total of 228 (62.81%) inadequacies were detected. As a result of the self-audit, 4.41% of treatments (16) were suspended and the dose of 58.4% of patients (212) was modified. CONCLUSION: There is a high percentage of patients with an inadequate prescription of ASA. This seems to be favoured by the low perception of the risk derived from a dose that, although inadequate, is considered ‘low’ by both the patient and the prescriber. Once more, pharmaceutical intervention has proven to be an effective tool in the detection and resolution of patient safety problems. REFERENCES AND/OR ACKNOWLEDGEMENTS: ASA data sheet. NICE guidance on antiplatelet therapy following myocardial infarction. No conflict of interest